"Doctors on the move": Exploring professionalism in the light of cultural transitions. (2nd September 2015) - McKimm, Judy; Wilkinson, Tim
Abstract: As the world becomes "flattened" and travel is easier, doctors and other health professionals move and live around the world in large numbers: some for short periods (such as student electives) others on a longer–term or permanent basis. Similarly, as wider migration patterns play out, all doctors need to learn to work in multi-cultural environments, whether they move countries or work in their "home country". We consider cross-cultural aspects of "professionalism" in terms of medical students' and graduates' assimilation into different cultures and some of the aspects of professional practice that may be problematic where cultural expectations and practices may differ. Specifically we explore professional socialization, identity formation, acculturation and cultural competency as related concepts that help our understanding of challenges for individuals and strategies for curriculum development or support mechanisms.